Islamic spirituality: the forgotten dimensions / Abang Hamizam and Ida Izumi Abdollah - Hamizam, Abang; Abdollah, Ida Izumi (Academy of Contemporary Islamic Studies (ACIS), 2016)
Relatively large number of spiritual assessment tools has emerged over the past years as a mean to assess individual spiritual wellbeing. The assessment tools however, are lacking of relevancy to Muslims. Unlike other ideologies, Islam is a divine system where the belief in Allah dictates all actions and behaviours of a Muslim in his daily life. The ninety-nine names of Allah or Asmaul Husna have been used as fundamentals for Muslims to nurture individual spiritual strength. Based on Asmaul Husna, this study re-evaluates the spirituality platform from an Islamic perspective. This empirical study describe the methodological development of the instrument to capture the spiritual factors in Islam. The proposed 35 items instrument has been empirically tested for unidimensionality, reliability, and validity using exploratory and confirmatory factor analysis. The Islamic spirituality factors are deeds, relationships, harmony, self-development, fairness, and compliance. The factors are distinct and conceptually clear. The study offers a systematic approach, a platform and a new insight towards the understanding of spirituality from an Islamic perspective.